2018
DOI: 10.1111/1756-185x.13331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of patient satisfaction and confidence on the success of treatment of combined rheumatic disease and interstitial lung disease in a multidisciplinary outpatient clinic

Abstract: MDDs afforded satisfactory management compared with standardized medical care. The MDD group felt better attention fromand satisfaction with medical staff, and had greater identification in their treatment. Further research engaging in MDDs with a comparable control group is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…HRCT was usually acquired only at baseline during the diagnostic process (24/27 studies). In 3 studies including longitudinal information, HRCT was repeated after 3–6 months in two studies (22, 31), and not specified in one study (35). Baseline chest X-ray was described in only one study (37).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HRCT was usually acquired only at baseline during the diagnostic process (24/27 studies). In 3 studies including longitudinal information, HRCT was repeated after 3–6 months in two studies (22, 31), and not specified in one study (35). Baseline chest X-ray was described in only one study (37).…”
Section: Resultsmentioning
confidence: 99%
“…PFT were not performed in the same two previously described studies, in which even HRCT was not performed (25, 39). In 21 studies, PFTs were performed only at the baseline while in 6 studies repetition was described during follow-up with different timing: 1–3 months (38), 3 months (22), 3–6 months (31), annually (27), and not specified (32). The parameters considered were in most cases the forced vital capacity (FVC), the ability to spread carbon monoxide (DLCO) and forced expiratory volume in the 1st second (FEV1); less frequently, total lung capacity (TLC); and residual volume (RV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of social support on psychological well-being has been preliminarily studied ( 124 ). Small observational studies in ILD have reported on general well-being indices, patient satisfaction, and perceived stress in the context of a mindfulness-based stress reduction program ( 125 127 ). Although this is a terrific start, more research is needed.…”
Section: Discussion Of Specific Patient-centered Outcomes and Research Recommendationsmentioning
confidence: 99%
“…The findings of high patient satisfaction appear to be consistent across disciplines with comparable results reported in multidisciplinary HIV, pediatric allergy, rheumatic disease, interstitial lung disease, and gender dysphoria clinics. 20-23…”
Section: Discussionmentioning
confidence: 99%